Clinical and laboratory parameters of pleural tuberculosis - Rashid, MM; Ghose, A; Islam, MB; Amin, R; Rahman, R; Faiz, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):191-8. The abstract of this article is available on the PubMed website